Peru Brand: a Nation under Construction? - Cuevas-Calderón, Elder (2016)
During the last decade Peru has experienced a euphoric rediscovery –pseudo revaluation as a country– due to its booming gastronomy, tourism and economic growth.In this context, the presentresearch uses semio-psychoanalytic and postcolonial theories to explain Peru’s social outlook regarding the concept of nation, its reunion with a non-existent identity and the construction of the idea of nation based on the marketing campaign titled the Peru Brand. Thus, Peru Brand, far from uniting all Peruvians and bring them together into the wellknown “melting pot”, becomes the resemantization of the old colonial discourse longing for a republic without natives. Therefore, in the Peru Brand advertising discourse, the “primitive natives” are white people brought from Nebraska and speak English.